Farming for the patchy Anthropocene: the spatial imaginaries of regenerative agriculture - Cusworth, G; Lorimer, J; Welden, EA (Wiley, 2023)
With its focus on the species level of the Anthropos, there is growing concern that the Anthropocene analytic lacks the conceptual nuance needed to grapple with the unevenly distributed harms and responsibilities tied up with issues of biodiversity loss, global warming, and land use change. Conceptual variants like the patchy Anthropocene have been proposed to better capture the justice implications of these socio-ecological crises, directing attention to their spatially ubiquitous yet context-specific character. The figure of the plantation has come to play an important role in this scholarship due to the contribution intensive agriculture had made to these interlinking crises. Through empirical study of the regenerative agricultural movement, this paper reflects on how regenerative farmers use different sites (fields, soils, livestock stomachs) to apprehend their agro-ethical responsibilities to more-than-human actors both near to and far from the landscapes they manage. Our aims here are two-fold. First, we provide a more affirmative account of agricultural management than is currently offered by plantation farming: a model of food production that is not just ‘in’ the Anthropocene, but ‘for’ it. Second, we contribute to ongoing discussions unfolding in the social sciences around the tools needed to conceptualise the interlinking spatial and justice aspects of the Anthropocene transition. By bringing the patchy analytic into conversation with more established geographic writing on scale, volume, and horizontal connections, we show the merit of juxtaposing multiple models of spatial relation as a way of gaining ethical and conceptual traction on complex socio-ecological issues. We argue that the ‘polymorphic’ spatial imaginaries of regenerative agriculturalists can offer some guidance on the tools needed to attend to the specificity of local Anthropocene outcomes in relation to socio-ecological forces actuating the world at much greater spatio-temporal scales.